Paciente de 13 años de sexo masculino que es llevado a la consulta por disminución progresiva de la visión asociada a una miopía degenerativa. - Bulgarin Tutiven, Anthony David (2021)
This clinical case highlights the importance of attending optometric consultations, which can be very helpful to prevent affectations in terms of permanent vision loss, for this reason this study focuses on a 13-year-old patient, who It has been presenting a progressive decrease in recent months, so he and his father attended consultation and it was possible to assess that this affectation may be associated with degenerative myopia. This visual decrease can be a cause of various ophthalmological pathologies, in which the origin can be determined anywhere in the visual pathway, from the ocular surface to the cortex organizes the light stimulus. For this reason, it is essential to develop a valid anamnesis together with the systemic eye examination in order to find a diagnosis avoiding unnecessary examinations. In this case, I identify a degenerative myopia which is characterized by presenting many diopters, in which the patient has a greater possibility of presenting ocular difficulties, in which it can cause early cataracts, glaucoma or chorioretinal atrophy, retinal degradation, Optic disc alteration, retinal detachment. The risk is more intense when the elongate is right in the eyeball, in which an advantage is that all the aforementioned conditions are effective treatments, but if control and care are not maintained, it can cause complications which can permanently compromise vision. of the patient.